Radiotherapy Interruption in Cancer Patients: Rates and Causes at Ahvaz Golestan Hospital - razmjoo, sasan; Haghi, Negar; Tahmasebi Birgani, Mohammad Javad; Arvandi, Shole; Hosseini, Seyed Mohammad; Shahbazian, Hodjatollah; javan, Mohammad reza (Asian Pacific Journal of Cancer Care, 2020)
Introduction: Radiotherapy is one of the most common cancer treatment modalities. The goal of this study was to establish the rates and causes of radiotherapy interruptions in cancer patients at Ahvaz Golestan Hospital. Methods: In this retrospective study, the data were collected during period from 2012 to 2013, from cancer patients who received radiation therapy at Golestan Hospital. Demographic characteristics and radiotherapy interruption frequency and reasons were reviewed and analyzed. Results: Among 1476 cases, 70.7% of patients had no radiotherapy interruption. The most common cause of treatment interruption was equipment damages and/or maintenance in 29.5% of patients. There were statistically significant relations between radiotherapy interruption with site of cancer (P=0.014) and living place of patients (P=0.006), respectively. Conclusion: Generally, treatment interruption at our center was not much higher than other centers; however, the most common cause of treatment interruption was equipment damages and/or maintenance, which was higher than most centers.